Genome Sequencing and Comparative Transcriptomics Provide a Holistic View of 4-Nitrophenol Degradation and Concurrent Fatty Acid Catabolism by Rhodococcus sp. Strain BUPNP1 - Sengupta, Kriti; Swain, Martin T.; Livingstone, Paul G.; Whitworth, David E.; Saha, Pradipta (Frontiers in Microbiology, 2019)
Rhodococcus sp.strain BUPNP1 can utilize the priority environmental pollutant 4-nitrophenol (4-NP) as its sole source of carbon and energy. In this study, genome and transcriptome sequencing were used to gain mechanistic insights into 4-NP degradation. The draft BUPNP1 genome is 5.56 Mbp and encodes 4,963 proteins, which are significantly enriched in hypothetical proteins compared to other Rhodococcus sp. A novel 4-NP catabolic 43 gene cluster “nph” was identified that encodes all the genes required for the conversion of 4-NP into acetyl-CoA and succinate, via 4-nitrocatechol. The cluster also encodes pathways for the catabolism of other diverse aromatic compounds. Comparisons between BUPN1 growing on either 4-NP or glucose resulted in significant changes in the expression of many nph cluster genes, and, during 4-NP growth, a loss of lipid inclusions. Moreover, fatty acid degradation/synthesis genes were found within the nph cluster, suggesting fatty acids may be concurrently catabolised with 4-NP. A holistic model for the action of the nph gene cluster is proposed which incorporates genetic architecture, uptake and metabolism of aromatic compounds, enzymatic activities and transcriptional regulation. The model provides testable hypotheses for further biochemical investigations into the genes of the nph cluster, for potential exploitation in bioremediation.